RULES FOR THE PREVENTION OF CONFLICTS BETWEEN TEACHERS AND STUDENTS IN THE CONTEXT OF EDUCATIONAL ACTIVITIES (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article discusses the causes of conflict between students and teachers and guidelines for their prevention, as well as practical suggestions and recommendations.